Predicting prolonged postoperative length of stay risk in patients undergoing lumbar fusion surgery: Development and assessment of a novel predictive nomogram - Lu, Chen-Xin; Huang, Zhi-Bin; Chen, Xiao-Mei; Wu, Xiao-Dan (Frontiers in Surgery, 2022)
Objective: The purpose of this study was to develop and internally validate a prediction nomogram model in patients undergoing lumbar fusion surgery. Methods: A total of 310 patients undergoing lumbar fusion surgery were reviewed and the median and quartile interval were used to describe PLOS. Patients with PLOS > P75 were defined as prolonged PLOS. The least absolute shrinkage and selection operator (LASSO) regression was used to filter variables for building the prolonged PLOS risk model. Multivariable logistic regression analysis was applied to build a predictive model using the variables selected in LASSO regression model. Area under the ROC curve (AUC) of predicting model was calculated and significant test was performed. Kappa consistency test between predictive model and actual diagnosis was performed. Discrimination, calibration, and clinical usefulness of the predicting model were assessed using the C-index, calibration plot, and decision curve analysis. Internal validation was assessed using the bootstrapping validation. Results: According to the interquartile range of PLOS in a total of 310 patients, the PLOS of 235 patients was ≤ P75 (7 days) (normal PLOS), and the PLOS of 75 patients was > P75 (prolonged PLOS). The LASSO selected predictors were used to build the prediction nomogram included BMI, diabetes, hypertension, duration of surgery, duration of anesthesia, anesthesia type, intraoperative blood loss, sufentanil for postoperative analgesia, and postoperative complication. The model displayed good discrimination with AUC value 0.807 (95% CI: 0.758–0.849, P<0.001), Kappa value 0.5186 (cut-off value, 0.2445, P < 0.001) and good calibration. High C-index value of 0.776 could still be reached in the interval validation. Decision curve analysis showed that the prolonged PLOS nomogram was clinically useful when intervention was decided at the prolonged PLOS possibility threshold of 3%. Conclusions: This study developed a novel nomogram with a relatively good accuracy to help clinicians access the risk of prolonged PLOS in lumbar fusion surgery patients. By an estimate of individual risk, surgeons and anesthesiologists may shorten PLOS and accelerate postoperative recovery of lumbar fusion surgery through more accurate individualized treatment.